An evaluation of the engineering book and periodicals collections of the Central Colleges of the Phillippines Library - Noces, Maria Juliana M.; Faderon, Rosalie B.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2018)
The objectives of this study were to find out the strengths and weaknesses of the engineering book and periodical collections in relation to the PACUCOA and PAARL standards; determine which areas of the engineering course offerings are served most effectively by the book and periodical collections are irrelevant to the curricula. Engineering book and periodical collections were mapped to the 20th edition of the Dewey Decimal Classification system.
This study conducted document analysis on the Central Colleges of the Philippines Library engineering and book collection and utilized the quantitative methods of collection size/growth and collection size standards and formulas using those of PAARL and PACUCOA; it also utilized the qualitative method of collection mapping. These methods are all collection-based.
After evaluating the book and periodical collections, the researcher came up with these findings: (1) The engineering book and periodical collections are strong for the courses in ECE, CpE, and EE: these are weak for the courses in CE, IE, and ME; (2)The engineering courses in ECE, CpE, and EE are served most effectively by the book and periodical collections while the courses in CE, IE, and ME are served minimally; (3) All the engineering book and periodical collections are relevant to the subject offerings and courses but both collections fall short of the PACUCOA and PAARL standards.
The researcher came up with the following recommendations: (1) Priority should be given to the following course: (a) The ME program has not been accredited yet by PACUCOA; in anticipation of the next accreditation visit to the college of engineering, acquisition of books and periodicals should be prioritized; and (b) Since IE and CE have only a small number of students, and they are served minimally, book and periodical collections should also be increased; (2) Even if ECE, CpE and EE courses are served effectively by the book and periodical collections and even if these collections are used interchangeably because of the nature of these subjects, there is still a need to enhance their collection even though they already meet the minimum standard requirement of PAARL but still fall short on some titles for the standards of PACUCOA; and (3) The CCP library should evaluate its engineering book and periodical collections annually, even if there is no accreditation scheduled, based on the PACUCOA and PAARL standards.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Central Colleges of the Philippines Library; Engineering -- Philippines -- Quezon City -- Periodicals -- Evaluation; Book -- Philippines -- Quezon City -- Evaluation